Dinamika Pengaruh Eksternal dalam Pengambilan Keputusan Kebijakan Pertahanan - Sarjito, Aris (CV Insan Kreasi Media, 2024)
In contemporary geopolitics, the formulation of defense policies is subject to a complex interplay of external factors, ranging from the influence of powerful actors to economic interests and ideational factors. This research aims to deepen our understanding of the external factors shaping defense policy decisions and their implications for national security strategies. Drawing upon qualitative research methods using secondary data analysis, this study investigates three key dimensions: